2019
DOI: 10.1155/2019/9790216
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Under-Five Pneumonia at Gondar University Hospital, Northwest Ethiopia: An Unmatched Case-Control Study

Abstract: Background Pneumonia causes about two million under-five deaths each year, accounting for nearly one in five child deaths globally. Knowing the determinants of under-five pneumonia is useful for prevention and intervention programs that are aimed to control the disease. Thus, the main aim of this study was to assess the determinants of under-five pneumonia at Gondar University Hospital, Ethiopia. Methods An institution-based unmatched case-control study was carried out from April 1 to April 30, 2015, taking a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 34 publications
4
26
0
1
Order By: Relevance
“…In this meta-analysis and systematic review, of the total 12 included studies, four studies were conducted from Amhara region [2,[22][23][24], four studies from Oromia region [25][26][27][28], two studies from SNNP [20,21], two studies from Addis Ababa [29,30] (Table 1).…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this meta-analysis and systematic review, of the total 12 included studies, four studies were conducted from Amhara region [2,[22][23][24], four studies from Oromia region [25][26][27][28], two studies from SNNP [20,21], two studies from Addis Ababa [29,30] (Table 1).…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…Pneumonia is defined as an acute infection of the lung parenchyma, which can be caused by many pathogens like viruses, bacteria and fungi [1,2]. Pneumonia is the leading cause of morbidity and mortality among underfive children [3].…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 summarizes the characteristics of the 34 included studies in the systematic review and metaanalysis (10,11,. 16 studies were found in Ethiopia (10,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), 8 in Kenya (11,(35)(36)(37)(38)(39)(40) 23 studies were cross-sectional, while the others used either case-control (n = 9) or cohort (n = 2) study design. Most of the studies 23/34(70.5%) were published between 2015 and 2019.…”
Section: Study Selectionmentioning
confidence: 99%
“…The questionnaires were developed objectives based on a different literature review. 16,17,18 It contains socio-demographic factors (age of the child, sex of child, residence, marital status of mother or caregiver, educational status of the mother or caregiver, religion, monthly income), and house factors (radio or TV in the house, number of house room and number of participants who live in the same house, the type of oor, and type of roof). It also contains childhood illnesses (history of vaccination, history of measles infection, history of HIV, and previous history of acute respiratory tract infections were reviewed from the child document).…”
Section: Data Collection Tools and Proceduresmentioning
confidence: 99%
“…14 On the other hand, deaths from pneumonia are higher in poor rural communities as a result of household air pollution, which depend on solid fuels (wood, dung or charcoal) for cooking or heating, overcrowded homes, and less likely to be immunized against measles and whooping cough, exposure to tobacco smoke, and malnutrition. 6,[15][16][17][18] The mortality of children is easily preventable and treatable through simple and cost-effective interventions. 19 Immunization, exclusive breastfeeding, appropriate complementary feeding, and proper hygiene are among preventive method [20][21][22] while the administrations of amoxicillin and/or antibiotic treatment are the curative methods which can save lives of children.…”
Section: Introductionmentioning
confidence: 99%